The Tourist Region and Globalisation Processes - Durydiwka, Małgorzata; Kowalczyk, Andrzej (Turyzm/Tourism, 2003)
The 'tourist region’ has long been a key term in geography and specifically in socio-economic geography. Among the many different types of region there is the tourist region characterised by spatial continuity and difference from surrounding areas. These characteristics however in the age of globalisation are no longer tourist region markers. In the face of tourist globalisation. the concept of a region gains new meaning because present-day tourist regions are largely open (due to international corporations like TUI AG which operate in them), show considerable unification of the tourist product they offer, and are not sufficiently continuous. This means that either the concept of a tourist region is becoming less clear-cut, or that in fact it is slowly losing its meaning.